Thermus aquaticus gen. n. and sp. n., a Nonsporulating Extreme Thermophile - Brock, Thomas D. (1969)
The isolation of a new thermophilic bacterium, Thermus aquaticus gen. n. and sp. n., is described. Successful enrichment requires incubation at 70 to 75 C, and the use of nutrient media relatively dilute with respect to the organic components. Strains of T. aquaticus have been isolated from a variety of thermal springs in Yellowstone National Park and from a thermal spring in California. The organism has also been isolated from man-made thermal habitats, such as hot tap water, in geographical locations quite distant from thermal springs. Isolates of T. aquaticus are gram-negative nonsporulating nonmotile rods which frequently form long filaments at supraoptimal temperatures or in the stationary phase. All isolates form a yellow cellular pigment, probably a carotenoid. A characteristic structure formed by all isolates is a large sphere, considerably larger than a spheroplast. These large spheres, as well as lysozyme-induced spheroplasts, are resistant to osmotic lysis. Deoxyribonucleic acid base compositions of four strains were determined by CsCl density gradient ultracentrifugation and found to be between 65.4 and 67.4 moles per cent guanine plus cytosine. The growth of all isolates tested is inhibited by fairly low concentrations of cycloserine, streptomycin, penicillin, novobiocin, tetracycline, and chloramphenicol. Nutritional studies on one strain showed that it did not require vitamins or amino acids, although growth was considerably faster in enriched than in synthetic medium. Several sugars and organic acids served as carbon sources, and either NH(4)(+) or glutamate could serve as nitrogen source. The organism is an obligate aerobe and has a pH optimum of 7.5 to 7.8. The optimum temperature for growth is 70 C, the maximum 79 C, and the minimum about 40 C. The generation time at the optimum is about 50 min. The possible relationships of this new genus to the myxobacteria, flexibacteria, and flavobacteria are discussed.